PENINJAUAN PENGARUH LABA BERSIH PADA JENIS MAKANAN DAN MINUMAN PERUSAHAAN DI BURSA EFEK INDONESIA - aminuddin aminuddin (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
This Paper described influence sales and expense promotion on net profit in food and beverages companies listed on The Indonesian Stock Exchange (IDX). This basic of sampling in this study used purposive sampling with a total sample of 10 companies, and it is processed by using IBM SPSS 24.0. The analysis showed variable sales and expense promotion has the ability to explain net profit in food and beverages companies listed on The Indonesian Stock Exchange (IDX) period 2015- 2018 by 85,6 % and 14,4 % is explained by variables other than the estimate. Sales and expense promotion the estimate influence significant and positive in net profit in food and beverages companies listed on The Indonesian Stock Exchange (IDX) period 2015-2018. Partially, variable sales the estimate influence significant in net profit and variable expense promotion the estimate not influence significant in net profit. Keywords : Sales, Expense Promotion, Net Profi